The Political Diplomacy of the Kingdom of Sikka with the Portuguese in the 16th and 17th Centuries - Deo Rany Bhetamex; Daya Negri Wijaya (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
The Kingdom of Sikka played a significant role in the political and economic development of Eastern Indonesia during the early period of contact with Europe, particularly through its diplomatic relations with the Portuguese and Netherlands. This study examines the background, objectives, and diplomatic strategies of the Sikka Kingdom in dealing with foreign influence. The objective of this study is to analyze how diplomacy was utilized by the Sikka Kingdom to secure trade benefits with the Portuguese and to strengthen its position as the primary political power in eastern Flores. The research method employed is the historical method, encompassing the stages of source collection, source criticism, interpretation, and historiography. The research sources utilized archival records, historical accounts, and supporting literature related to the Sikka Kingdom’s diplomacy with the Portuguese. The results of the study indicate that the Sikka Kingdom’s diplomacy was adaptive, enabling it to establish mutually beneficial trade relations, access European goods, and enhance its political legitimacy through an alliance with the Portuguese. These diplomatic relations helped the Sikka Kingdom strengthen its dominance over the region and maintain its influence in the surrounding areas. In conclusion, diplomacy served as a crucial tool for the Sikka Kingdom to integrate economic and political interests in maintaining and expanding its power at the regional level.